(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
The research work presents the use of genetic algorithm method coupled with optidesigner software for the optimal design of existing NDA water distribution network consisting of 63 pipes of different materials, 57 junctions, 3 tanks and two source reservoirs. After several runs, the cost obtained from this network using optidesigner software under the application of genetics algorithm was 130,450, with minimum pressure head of 3m and maximum of 100, Pressure penalty of 200,000 and probability of mutation equal to 0.03, also the commercial diameters of 4”, 6”, 8”, 10”, 12”, 14”, 16” 18” 20’’, 22’’and 24’’ dmin =4”, dmax = 24” were used for the distribution network during the optimization process. A feasible solution that can supply water at adequate pressure was obtained